[en] A COMPARISON OF IDENTIFICATION METHODS WITH APPLICATION TO STATE ESTIMATION - ABILIO PEREIRA DE LUCENA FILHO (MAXWELL, 2008)
[pt] Este trabalho trata da comparação de quatro de métodos de identificação paramétrica para sistemas dinâmicos lineares, operando em ambiente estocástico. Dos métodos envolvidos, três são de correlações, enquanto um é uma derivação do método de mínimos quadrados. Inicialmente, foi apresentado o problema de identificação de sistemas, e são discutidos aspectos estruturais ligados à ele. A seguir é apresentado um resumo de cada método e efetuada a comparação entre eles, tanto sob o ponto de vista estrutural quanto computacional. Nesta última fase, foram feitas simulações, e utilizado dados reais. === [en] This work presents a comparison of effectiveness of form parametric identification methods for linear dynamical systems operating in a stochastic environment. Three of these methods are correlation ones, and the other is derived from the least squares method. First of all, the system identification problem was introduced, and then, the structural aspects related to it were discussed. Later on, it was presented a review ot the above mentioned methods as well as a comparison between them. Such a comparison was concerned both with structural and computational aspects. This last stage uses simulated and real data.